Dr. Ambedkar Buddhism and social change (Delhi Buddhist World Press, 2017)
Dr. B.R. Ambedkar (1891-1956), a multidimensional personality, is often hailed as the Chief Architect of the Indian Constitution. But one of the most abiding aspect of his life and career which history will remember is his conversion to Buddhism, leading the largest one-time conversion of a people. Therefore, his contribution to, and interpretation of. Buddhism, and his role in its revitalization and above all his use of Buddhism as an instrument of social change in India are subjects of prime importance and serious study. This volume contains twelve select papers presented at or prepared for an International Workshop organized by the Bhikku Jagdish Kashyap Institute of Buddhist and Asian Studies at Sarnath in March 1991. In an alphabetical order, the scholars and the titles of their contributions are : - D.C. Ahir, "Dr. Ambedkar's Pilgrimage to Buddhism" - Trimothy Fitzgerald, "Buddhism in Maharashtra : A Tripartite Analysis : A Research Report" - K.N. Kadam, "Dr. Ambedkar and Buddhism as an Instrument of Social Change" - Lokamitra, "Sangha and Social Change" - N.G. Meshram, "Dr. Ambedkar the Liberator" - A.K. Narain, "Dr. Ambedkar, Buddhism and Social Change : A Reappraisal" - Christopher S. Queen, "Ambedkar, Modernity and the Hermeneutics of Buddhist Liberation" - Geoffrey P. Redmond, "Is there a Specifically Buddhist Approach to Social Ethics" - Valerian Rodrigues, "Between Tradition and Modernity : The Gandhi-Ambedkar Debate" - A.V. Satish Chandra, "The Annihilation of Caste : The Unfinished Task of Dr. Ambedkar" - Gary Michael Tartakov, "Art and Identity : The Rise of a new Buddhist Imagery" - Eleanor Zelliot, "New Voices of the Buddhists of India"
Keywords: Buddhism; Religious Mythology; Social Theology; Narain, A. K. and Ahir, D. C. ed.; Dr. B. R. Ambedkar (1891-1956)